Network Creative Activities in the Context of Hermeneutic Cultural Studies - Yu. O. Pichugina (Культура України, 2019)
The aim of this paper is to conceptualize the potential of network creative activities in the context of hermeneutic cultural studies. Research methodology is based on the principles of system approach, which contributes to a comprehensive understanding of changes within culture that are caused by intensive technological development of modern society. Phenomenological method makes it possible to consider network creative activities as a phenomenon of modern culture. Hermeneutic approach makes it possible to interpret the inherent meanings in the works of network creative activities. Results. The author investigates a new phenomenon of network creative activities, which remains an unexplored field in cultural studies. The works of network creative activities (Internet memes, photos in social networks, comments on them) are analyzed in three contexts: personal, social and universal. The potential of network creative activities has been interpreted, which is particularly significant in the context of hermeneutic cultural studies. When creative products are interpreted, the knowledge of a historical epoch, its cultural traditions, universals and world perception is gained. Thus, the researcher approaches the comprehension of modern civilization by studying the artefacts of the network culture. Novelty. The potential of network creative activities in the context of hermeneutic cultural studies has not been the subject of the culturological analysis yet. The author substantiates the idea of this subject by studying it in the context of hermeneutic cultural studies. The practical importance. Hermeneutics is defined as an effective approach to the comprehension of network culture, and network creative activities are defined as an additional methodological apparatus of hermeneutical research. It enables to speak about the extension of scope of methodological apparatus of philosophical hermeneutics and to outline the prospects for the development of a separate line of cultural studies — culturological hermeneutics.